Spontaneous segregation of a heterozygous diploid of Aspergillus niger - Das, A; Ilczuk, Z (Folia microbiologica, 1978)
A case of spontaneous segregation of a heterozygous diploid was observed with Aspergillus niger, giving rise to a somatic recombinant. Assuming an independence of markers, its genotype is suggested to be brw+lys pab+brw lys+pab.
Keywords: rekombinace genetická; Genetic Linkage; mutace; genotyp; Ultraviolet Rays; Diploidy; Mutation; Genotype; genetická vazba; Recombination, Genetic; Aspergillus niger; ultrafialové záření; diploidie